Analysis of Student Learning Outcomes in View of Mathematical Ability and Ability Chemistry Class XI Science Students at Madrasah Aliyah Swasta (MAS) Proyek Univa Medan on Buffer Solution Material - Azizah, Meilani; Khairunisa, Dira; Rangkuti, Maisyaroh; Juwita, Intan; Panggabean, Freddy Tua Musa (Jurnal Pendidikan dan Pembelajaran Kimia, 2023)
Analysis of Student Learning Outcomes in View of Mathematical Ability and Ability Chemistry Class XI Science Students at Madrasah Aliyah Swasta (MAS) Proyek Univa Medan on Buffer Solution Material.The aim of this research is to determine the mathematical abilities and analytical abilities of students in class XI IPA Madrasah Aliyah Swasta (MAS) Proyek Univa Medan on Buffer Solutions material. This type of research is cause and effect research. The data collected was in the form of mathematical ability test instruments, chemical analysis ability tests and student learning outcomes tests based on Low Order Thinking Skills (LOTS) and High Order Thinking Skills (HOTS). The results of the analysis show that students have an average mathematical ability of 64.00 and an average student analytical ability of 63.24. Student chemistry learning outcomes in buffer solution material have an average of 47.00. Analysis of students' answer sheets on learning outcomes tests shows that students do not have good mathematical skills and analytical skills, shown by a percentage of 57%. This data also shows that students' difficulties with buffer solution material are due to students not understanding chemical concepts. DOI: 10.23960/jppk.v12.i3.23.13